Detecting Deadlocks in Concurrent Systems - Fajstrup, Lisbeth; Raussen, Martin (BRICS Report Series, 1996)
We use a geometric description for deadlocks occurring in scheduling problems for concurrent systems to construct a partial order and hence a directed graph, in which the local maxima correspond to deadlocks. Algorithms finding deadlocks are described and assessed. Keywords: deadlock, partial order, search algorithm, concurrency, distributed systems.